Octocorals in the Gulf of Aqaba exhibit high photosymbiont fidelity - Liberman, Ronen; Benayahu, Yehuda; Huchon, Dorothée (Frontiers in Microbiology, 2022)
Symbiotic associations, widespread in terrestrial and marine ecosystems, are of considerable ecological importance. Many tropical coral species are holobionts, formed by the obligate association between a cnidarian host and endosymbiotic dinoflagellates of the family Symbiodiniaceae. The latter are abundant on coral reefs from very shallow water down to the upper mesophotic zone (30-70 meters). The research on scleractinians has revealed that the photosymbiont lineages present in the cnidarian host play an important role in the coral’s ability to thrive under different environmental conditions, such as light regime and temperature. However, little is known regarding octocoral photosymbionts, and in particular regarding those found deeper than 30 meters. Here, we used ribosomal (ITS2) and chloroplast (23S) markers to uncover, for the first time, the dominant Symbiodiniaceae taxa present in 19 mesophotic octocoral species (30-70 meters depth) from the Gulf of Aqaba/ Eilat (northern Red Sea). In addition, using high-throughput sequencing of the ITS2 region we characterized both the dominant and the rare Symbiodiniaceae lineages found in several species across depth. The phylogenetic analyses of both markers were in agreement and revealed that most of the studied mesophotic octocorals host the genus Cladocopium. Litophyton spp. and Klyxum utinomii were exceptions, as they harbored Symbiodinium and Durusdinium photosymbionts, respectively. While the dominant algal lineage of each coral species did not vary across depth, the endosymbiont community structure significantly differed between host species, as well as between different depths for some host species. The findings from this study contribute to the growing global-catalogue of Cnidaria-Symbiodiniaceae associations. Unraveling the Symbiodiniaceae composition in octocoral holobionts across environmental gradients, depth in particular, may enable a better understanding of how specialized those associations are, and to what extent coral holobionts are able to modify their photosymbionts.